Research trends in nutrition and exercise for sarcopenic obesity: a bibliometric analysis - Zhang, Guoqing; Hu, Juncui; Chen, Chanjuan; Zhu, Wenyan; Chen, Yingyi; Cheng, Yi; Hu, Wen; Rao, Zhiyong (Frontiers in Nutrition, 2025)
ObjectivesWith global population aging and obesity rates rising, the prevalence of sarcopenic obesity (SO) is being rapidly increased, resulting in significant health impacts and making it a growing public health concern in academic circles. Exercise and nutrition are crucial in the etiology, prevention, and management of SO; therefore, bibliometric research in this field can provide key insights for future scientific inquiry.MethodsThe literature concerning on nutrition and exercise in SO published over the past 20 years and indexed in the Web of Science Core Collection database and Scopus database was screened, and bibliometric analyses were subsequently conducted using CiteSpace and VOSviewer.ResultsA total of 658 literatures were selected for bibliometric analysis. A steady rise in publications in this field over 20 years was shown by the results, with major contributions being made by China and the US. The most literatures were published by the University Clermont Auvergne, with Professor Yves Boirie being identified as the most prolific author. The journal Nutrients accounted for the most publications. Exercise research appeared earliest, with nutritional intervention gaining attention in recent years. Research frontiers over the past 5 years have primarily focused on three main themes: exercise and nutritional interventions, the exploration of pathophysiological mechanisms, and the establishment of clinical guidelines, with “osteosarcopenic obesity” being a prominent and emerging area of research.ConclusionThis study provides a comprehensive overview of the current state of nutrition and exercise research in SO.